Effects of Center-Based Delivery of Tai Chi and Qi Gong Group Classes on Self-Reported Symptoms in Cancer Patients and Caregivers. (July 2020) - Lopez, Gabriel; Narayanan, Santhosshi; Christie, Aimee; Powers-James, Catherine; Liu, Wenli; Garcia, M Kay; Gomez, Telma; Wu, Jimin; Chunduru, Aditi; Williams, Janet L.; Li, Yisheng; Bruera, Eduardo; et al.
Background: There is increasing interest in complementary approaches such as Tai Chi (TC) and Qi Gong (QG) in oncology settings. We explored the effects of TC/QG delivered in group classes at a comprehensive cancer center.Methods: Patients and caregivers who participated in TC or QG completed assessments before and after an in-person group class. Assessments included questions about expectancy/satisfaction and common cancer symptoms (Edmonton Symptom Assessment Scale [ESAS]). ESAS distress subscales analyzed included global (GDS), physical (PHS), and psychosocial (PSS).Results: Three hundred four participants (184 patients, 120 caregivers) were included in the analysis. At baseline, caregivers had a greater expectancy for change in energy level as a result of class participation compared with patients (22.9% vs 9.9%). No significant difference was observed between baseline patient and caregiver PSS. Clinically significant improvement in well-being was observed among patients in TC classes (1.0) and caregivers in QG classes (1.2). For fatigue, patients (1.4) and caregivers (1.0) participating in QG experienced clinically significant improvement. Both TC and QG classes were associated with clinically significant improvements (ESAS GDS decrease ≥3) in global distress for patients (TC = 4.52, SD= 7.6; QG = 6.05, SD = 7.9) and caregivers (TC = 3.73, SD = 6.3; QG = 4.02, SD = 7.8). Eighty-nine percent of participants responded that their expectations were met.Conclusions: Patients and caregivers participating in TC or QG group classes were satisfied overall and experienced significant improvement in global distress. Additional research is warranted to explore the integration of TC and QG in the delivery of supportive cancer care.